Isomerization of various aldo-saccharides to the corresponding keto-saccharides under microwave heating using uncalcined scallop shell powder as a catalyst - Watanabe, Yoshiyuki; Kobayashi, Takashi; Khuwijitjaru, Pramote; Adachi, Shuji (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
Fifty milliliters of 0.2 mol/L aqueous solutions containing two aldo-pentoses (ribose and xylose), two aldo-hexoses (glucose and galactose), and two aldo-disaccharides (cellobiose and lactose) were placed in a pressure-resistant vessel along with 0.5 g of uncalcined scallop shell powder and heated by a microwave oven at 700 W to isomerize the aldo-saccharides to the corresponding keto-saccharides (ribulose and xylulose, fructose and tagatose, and cellobiulose and lactulose). The yields of keto-saccharides were approximately 10 % for pentoses, 18 % for hexoses, and 25 % for disaccharides within 105 s. The selectivity from aldo-saccharide to the keto-saccharide followed the order of disaccharide > hexose > pentose. Measurements were taken for pH, calcium ion concentration, and absorbance at 280 nm and 420 nm. The acidic by-products formed during heating were neutralized by the shell powder, maintaining the pH of the reaction mixture above 7 to promote isomerization through Lobry de Bruyn–Alberda van Ekenstein transformation.